(untitled) (American International Journal of Humanities, Arts and Social Sciences, 2019)
The study demonstrated the impact of disaggregated public expenditure on unemployment rate in selected African countries with panel data spanning from 2000 to 2017. The data were majorly sourced from the World Bank Indicator. The study employed Generalized Method of Moments (GMM) techniques for empirical analysis. The findings of two-step system GMM showed that expenditure on infrastructure and education reduce unemployment rate, while expenditure on defense and health increase unemployment rate in the region. The short-run elasticity estimate showed that infrastructure and education expenditures reduce unemployment rate by 9% and 1.83%. A unit rise in defense and health expenditure increase unemployment rate by 5.2% and 84.5%. The long-run elasticity of infrastructure and education expenditure reduce unemployment rate by 3.8% and 7.89 %, while the long-run defense and health expenditure elasticity’s increase unemployment rate by 22.22% and 364.58% in the selected African countries. The policy implication is that, the positive relationship between expenditure on health and unemployment could be attributed to mismanagement of government funds due to corruption, while that of defense and unemployment could be high rate of insecurity and crimes in the region. Therefore, the study recommended among others a drastic measure to further improve the education sector through adequate investment in education that will help in skills, development and training.